Work to family enrichment as mediator between organizational support and employees performance - Aneel Kumar; Khalil Ahmed Channa; Muhammad Waqas Maharvi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
This study investigates the relationship between work to family organizational support and employees' performance, mediated by work to family enrichment. It analyses primary data, collected from the various commercial banks, operating in Sindh, Pakistan (N=401). A five point Likert type of survey questionnaire was distributed to respondents. The study applies the structural equation modeling approach (SEM) for data analysis purpose. Mediation analysis has been conducted following the procedure of Preacher and Hayes (2004, 2008) and Rucker, Preacher, Tormala, & Petty (2011). Results show the significant main effect of work to family organizational support and the indirect effect, through work to family enrichment on employees' performance. Overall, this study establishes work to family enrichment as the missing link in the relationship between work to family organizational support and employees' performance. The study contributes theoretically by incorporating the role of social exchange theory and work family enrichment theory. Empirical contribution of this study is to confirm the effect of work to family organizational support on employees' performance and work to family enrichment as the mediator.
Keywords: 330; work to family organizational support; work to family enrichment; work performance (in-role behavior); social exchange theory; bank employees